2015
DOI: 10.5812/jjm.15779
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Hydrops Due to Viral Hepatitis A Infection: A Case Report

Abstract: Introduction:Acute Hepatitis A Virus (HAV) infection is common in the developing countries among children, but hydrops of gallbladder due to hepatitis A infection is an uncommon presentation.Case Presentation:A five-year-old boy was admitted in Namazi Hospital, Shiraz, Iran due to jaundice and severe abdominal pain for 10 days. Physical examination revealed a mass in the right upper quadrant with severe tenderness. Liver function tests were abnormal while other laboratory data such as blood urea nitrogen, seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that hepatitis A virus (HAV) infection is associated with acute acalculous cholecystitis in children and adults [56,57]. In these cases, higher elevations of the ALT levels of more than 500 IU/L are occasionally observed [58][59][60][61][62][63][64][65][66][67][68][69]. Cholestasis is likely to be associated with HAV infection [57].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hepatitis A virus (HAV) infection is associated with acute acalculous cholecystitis in children and adults [56,57]. In these cases, higher elevations of the ALT levels of more than 500 IU/L are occasionally observed [58][59][60][61][62][63][64][65][66][67][68][69]. Cholestasis is likely to be associated with HAV infection [57].…”
Section: Discussionmentioning
confidence: 99%
“…After identifying 671 articles, 153 articles involving 171 cases were eligible: 104 viral infection and 67 rheumatic disease AAC patients. [8,11–162] Viral infection types included: Epstein Barr virus, hepatitis virus, dengue virus, SARS-CoV-2 (COVID-19), human immunodeficiency virus, and cytomegalovirus. Rheumatic diseases included: systemic lupus erythematosus, adult-onset Still disease, Henoch-Schönlein purpura, polyarteritis nodosa, Churg-Strauss syndrome (eosinophilic granulomatosis with polyangiitis), microscopic polyangiitis, temporal arteritis, Wegener granulomatosis (granulomatosis with polyangiitis), Kawasaki syndrome, systemic juvenile idiopathic arthritis, and juvenile dermatomyositis (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Gallbladder involvement has been described in 50 to 98 % of adults with acute viral hepatitis, mild gallbladder wall thickening being the most common sonographic finding [7]. However HAV induced HG has been very rarely reported in children [1,2,[6][7][8][9][10] . Although the origin is obscure, demonstrated invasion of the gallbladder and bile duct epithelium by HAV and cellmediated immunologic response have been proposed in the pathogenesis of HAV infection induced cholecystitis [3,11,12].…”
Section: Discussionmentioning
confidence: 99%